Do penalty-based pay-for-performance programs improve surgical care more effectively than other payment strategies? A systematic review. (December 2020) - Kim, Kyung Mi; Max, Wendy; White, Justin S.; Chapman, Susan A.; Muench, Ulrike
Abstract: Background: The aim of this systematic review is to assess if penalty-based pay-for-performance (P4P) programs are more effective in improving quality and cost outcomes compared to two other payment strategies (i.e., rewards and a combination of rewards and penalties) for surgical care in the United States. Penalty-based programs have gained in popularity because of their potential to motivate behavioral change more effectively than reward-based programs to improve quality of care. However, little is known about whether penalties are more effective than other strategies. Materials and methods: A systematic literature review was conducted according to the PRISMA guideline to identify studies that evaluated the effects of P4P programs on quality and cost outcomes for surgical care. Five databases were used to search studies published from 2003 to March 1, 2020. Studies were selected based on the PRISMA guidelines. Methodological quality of individual studies was assessed based on ROBINS-I with GRADE approach. Results: This review included 22 studies. Fifteen cross-sectional, 1 prospective cohort, 4 retrospective cohort, and 2 case-control studies were found. We identified 11 unique P4P programs: 5 used rewards, 3 used penalties, and 3 used a combination of rewards and penalties as a payment strategy. Five out of 10 studies reported positive effects of penalty-based programs, whereas evidence from studies evaluating P4P programs with a reward design or combination of rewards and penalties was little or null. Conclusions: This review highlights that P4P programs with a penalty design could be more effective than programs using rewards or a combination of rewards and penalties to improve quality of surgical care. Highlights: Evidence on the effectiveness of pay-for-performance programs in quality improvement is mixed. Five out of 10 studies reported positive effects of penalty-based programs. Evidence from studies evaluating P4P programs with a reward design or combination of rewards and penalties was little or null. The increasing use of penalty-based pay-for-performance programs has the potential to improve surgical care quality. Penalties may induce stronger provider and hospital behavioral change than other payment strategies.